Bosnian War Horrors: Dr. Haris Silajdzic
How U.S. is routinely invited to go into troubled countries and settle their problems by force if necessary. Should they do that? Why? Why did U.S. go into Somalia but not Bosnia? Dr. Silajdzic, Bosnian Foreign Minister, answers question, "What do you want U.S. to do?"